Evaluation of Seismic Performance of Multistorey Building With Floating Column - Prateek Kumar (AG Volumes, 2021)
The current study deals with utilization of space such as basements, parking areas/recreational hall under building etc. as well as in terms of elevation of building; for this reason, a study of floating columns is necessary for earthquake safety. Finding the influence of floating columns given at various positions on seismic response and determining the optimum placement for floating columns where the structure can resist with the least likelihood of failure for RCC buildings. The primary goal of this research is to use the response spectrum approach to do seismic analysis on an RC building in order to better use the available space.